Attitudes of young people in the Republic Srpska about marriage, family and parenthood - Košarac, Biserka (Napredak, 2023)
The subject of this paper involves the attitudes of the student population in Republic Srpska about marriage, family and parenthood. Changes in family domain in modern society directly affect not only the everyday lives of individuals, but also society as a whole. Negative demographic trends, structural problems of the Republic Srpska society, as well as the spread and acceptance of value orientations from the West also affect changes in marriage and family in our society. This paper analyses data from a survey of young people’s attitudes about marriage, family and parenthood, and their relations with some basic sociodemographic characteristics. Moreover, young people’s plans for their future life, forming their own families and having children, have also been analysed.
Keywords: marriage; family; parenthood; attitudes